Model Struktural Pengembangan Minat Berwirausaha Pada Mahasiswa Semester Akhir di Kota Medan - Edy Sahputra Sitepu; Safaruddin Safaruddin (Valid: Jurnal Ilmiah, 2020)
This study aims to produce a structural equation model of the development of entrepreneurial intention among students, especially the final year students in various higher education institutions in the city of Medan. The variables used are the family environment, the environment around each as an exogenous factor, while personality factors, motives and intentions for entrepreneurship as endogenous factors. Personality factors and motives become intervening variables. The number of respondents was 240 people taken based on a purposive random sampling approach from 12 campuses in the city of Medan. It is hoped that this research can contribute a number of contributions and input to the formulation of local government policies in encouraging targets for achieving young entrepreneurial growth and minimizing the unemployment rate, especially in Medan City. The results showed that the variable family environment and surrounding environment directly had a positive effect on student entrepreneurial intention. The family environment and the surrounding environment directly have a positive effect on student entrepreneurial personality. The family and neighbourhood environment directly has a positive effect on student entrepreneurship motives. The family environment and surrounding environment indirectly have a positive effect on student entrepreneurial intention through the intervening variable of entrepreneurial personality. The family environment and the surrounding environment indirectly have a positive effect on student entrepreneurial interest through intervening variables of personality and entrepreneurial motives.